2012
DOI: 10.1097/aud.0b013e31822ccba0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ear-Canal Reflectance and Umbo Velocity in Patients With Conductive Hearing Loss: A Preliminary Study

Abstract: Objective The goal of the present study was to investigate the clinical utility of measurements of ear-canal reflectance (ECR) in a population of patients with conductive hearing loss in the presence of an intact, healthy tympanic membrane (TM) and an aerated middle ear. We also sought to compare the diagnostic accuracy of umbo velocity (VU) measurements and measurements of ECR in the same group of patients. Design This prospective study comprised 31 adult patients with conductive hearing loss, of which 14 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
94
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 27 publications
(39 reference statements)
11
94
0
4
Order By: Relevance
“…Using the tympanometry, the audiologists can diagnose some middle ear diseases including otitis media, perforation of the TM and problems with the Eustachian tube [7,8]. However, tympanometry has limited sensitivity in detecting various middle ear diseases (i.e., many patients with middle ear diseases have normal tympanogram) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Using the tympanometry, the audiologists can diagnose some middle ear diseases including otitis media, perforation of the TM and problems with the Eustachian tube [7,8]. However, tympanometry has limited sensitivity in detecting various middle ear diseases (i.e., many patients with middle ear diseases have normal tympanogram) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Although the variability observed in normative data is smaller than the differences observed between these data and data from ears with middle-ear pathologies (e.g., Voss et al, 2012;Nakajima et al, 2012), the variability affects the diagnostic value of WAI, especially considering that the diagnosis of middle pathologies using absorbance, for example, is based on comparison of the shape of the absorbance functions in patient ears to a normative reference absorbance function. It is important to limit the contribution to this variability that is due to the measurement system.…”
Section: Introductionmentioning
confidence: 83%
“…Reflectance has been observed to be sensitive to abnormal middle-ear states such as (1) positive and negative pressure in the middle-ear cavity, (2) a fluid-filled middle ear, (3) malleus or stapes fixation, (4) incudostapedial-joint disarticulation, (5) tympanic-membrane perforations, and (6) superior semicircular canal dehiscence. Because of its sensitivity to these pathological conditions, reflectance has been suggested for clinical diagnosis of various middle-ear disorders (e.g., Voss et al, 2012;Nakajima et al, 2012;Rosowski et al, 2012;Merchant, 2014;Merchant et al, 2015). However, reflectance measurements made with different measurement systems and made in different research laboratories can be variable.…”
Section: Introductionmentioning
confidence: 99%
“…Results [1,2] showed that small increases in |ECR| 2 at low-to-mid frequencies (400-1000 Hz) were found in patients with stapes fixation, and distinct narrow-band decreases were seen for patients with both SCD (notch around 1000 Hz) and ossicular discontinuity (larger notch at 600-800 Hz). SCD patients tended to have smaller air-bone gaps at high frequencies compared to patients with stapes fixation and ossicular discontinuity.…”
Section: Discussionmentioning
confidence: 99%
“…Thirtyone of these patients were confirmed to have CHL due to stapes fixation, ossicular discontinuity, or superior semicircular canal dehiscence (SCD). Confirmation of the etiology responsible for the CHL was made surgically for both ossicular pathologies, and using a combination of high-resolution computed tomography imaging and vestibular evoked myogenic potential for SCD.Results [1,2] showed that small increases in |ECR| 2 at low-to-mid frequencies (400-1000 Hz) were found in patients with stapes fixation, and distinct narrow-band decreases were seen for patients with both SCD (notch around 1000 Hz) and ossicular discontinuity (larger notch at 600-800 Hz). SCD patients tended to have smaller air-bone gaps at high frequencies compared to patients with stapes fixation and ossicular discontinuity.…”
mentioning
confidence: 99%